Has the amount of available financial resources become the predominant factor in sporting clubs’ successes and that of a country’s national team? The case of Turkish basketball clubs - (:unkn) unknown (Springer International Publishing, 2017)
If we compare the economic rankings of countries to that of their national sports results, we notice that there is a strong correlation between the two. Indeed, the top 10 ranked economically find themselves in part, but only in part, at similar rankings on the sporting level. India and Brazil do not transform their economic performances on the sporting chart; Russia and Australia are better ranked on the sporting scale than from an economic point of view. We must note that the idea that sporting success principally means economic investment is a fairly recent observation and one that should be nuanced if we take the example of soccer in which clubs and national teams from smaller countries like the Netherlands or Portugal have excelled even when faced with large, economically strong nations like Germany, Great Britain, or France. It seems that the market’s globalization as well as the sporting competition is a part of the explanation because it necessitates more and more cumbersome investments. But, public funding no longer suffices to finance sporting events and it is sometimes badly used by bureaucrats who lack expertise. As a result, the solution ends up being private funding from renowned enterprises that are efficient on the competitive markets. However, the funding capacity of enterprises is directly linked to the economic conjuncture of countries where the funding capacity develops. Turkey (classified 17th in the world on an economic scale and 41st on a sporting scale at Rio in 2016) constitutes a good illustration of this complex relationship between economic means and sporting results. The results of Turkey’s basketball clubs attract attention. The qualification of the Fenerbahçe club during the last three ULEB Euroleague Final Four (2015, 2016 and 2017) and its Euroleague Final Four’s title at the last edition (2017), or moreover Galatasaray’s victory in the ULEB Eurocup (2016) represent exceptional successes that surprise sports analysts. However, behind these sporting achievements, privately funded money appears, given by sponsors who financed the construction of new sports halls and the recruitment of players on an international level. The sporting expenses of Turkish enterprises during the last 10 years have increased considerably, in relation to the good economic health of the country. We propose an analysis of the link between economic resources and sporting performance, applied to the case of sports in Turkey, in order to show the complexity of this issue. We shall see that the hypothesis of a direct explanatory influence is not always valid and that other factors should be taken into consideration. © Springer International Publishing 2017.
Keywords: Budgets of sports clubs; Sporting results; Sports economics; Sports sponsorship